2008
DOI: 10.2337/db07-1062
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Role of Interleukin-6 in Regulating Insulin Sensitivity in Murine Skeletal Muscle

Abstract: OBJECTIVE-Cytokines are elevated in various insulin-resistant states, including type 2 diabetes and obesity, although the contribution of interleukin-6 (IL-6) in the induction of these diseases is controversial.RESEARCH DESIGN AND METHODS-We analyzed the impact of IL-6 on insulin action in murine primary myocytes, skeletal muscle cell lines, and mice (wild type and proteintyrosine phosphatase 1B [PTP1B] deficient).RESULTS-IL-6 per se increased glucose uptake by activating serine/threonine protein kinase 11 (LK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(121 citation statements)
references
References 54 publications
7
105
0
2
Order By: Relevance
“…Acute IL-6 treatment increased glucose uptake, while chronic exposure resulted in insulin resistance owing to activation of JNK and impairment of insulin signalling on the level of IRS-1 [15]. Interestingly, in vivo animal studies revealed that chronically elevated serum levels of IL-6 serum induced by either treatment with recombinant protein [16] or using a transgenic approach [17] improved whole body glucose tolerance and insulin sensitivity, which might be linked to augmentation of central leptin action.…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute IL-6 treatment increased glucose uptake, while chronic exposure resulted in insulin resistance owing to activation of JNK and impairment of insulin signalling on the level of IRS-1 [15]. Interestingly, in vivo animal studies revealed that chronically elevated serum levels of IL-6 serum induced by either treatment with recombinant protein [16] or using a transgenic approach [17] improved whole body glucose tolerance and insulin sensitivity, which might be linked to augmentation of central leptin action.…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
“…As summarised in Table 1, in vitro studies have shown that IL-6 increases myotube fatty acid oxidation and lipolysis via AMPK activation [32,33]. [46] No data available regarding endocrine metabolic effects of muscle-derived BDNF IL-6 ↑ GLUT4 translocation [19,20] ↑ Glucose uptake [15,19] ↑ Glycogen synthesis [18,20] ↑ Fatty acid oxidation [18][19][20] ↑ Lipolysis [32][33][34] Liver: ↑ Glucose production [23] Intestine: ↑ GLP-1 secretion of L cells [52] Pancreas: ↑ Beta cell proliferation [52] ↑ GLP-1 secretion of alpha cells [52] ↑ Proliferation and ↓ apoptosis of alpha cells [51] IL-13 ↑ Glucose uptake [28] ↑ Glucose oxidation [28] ↑ Glycogen synthesis [28] Liver: ↓ Glucose production [29] IL-15 ↑ Fatty acid oxidation [43] Adipose tissue: ↓ Lipid accumulation [44,45] ↑ Adiponectin secretion [44] Irisin No data available Adipose tissue: ↑ White to brown shift [98,111] No effect on browning [100] FGF21 ↑ Glucose uptake [99,136] Adipose tissue: ↑ White to brown shift [99] ↑ Glucose uptake [99] ↑ Adiponectin secretion [127,128] Liver: ↑ Fatty acid oxidation [137] ↑ Gluconeogenesis [137] Recently, a study using isolated mouse muscle reported that IL-6...…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, the absence of NOD1 and NOD2 attenuates diet-induced insulin intolerance, and NOD1 ligands induce wholebody insulin resistance (Schertzer et al 2011). IL6 is one of several pro-inflammatory cytokines that have been associated with insulin resistance and type 2 diabetes (Kern et al 2001, Pradhan et al 2001, Senn et al 2002, Nieto-Vazquez et al 2008. High levels of IL6 are also associated with GDM (Yu et al 2007, Kuzmicki et al 2009, Morisset et al 2011.…”
Section: Figurementioning
confidence: 99%
“…Chronically elevated levels of IL-6 are associated with the development of type 2 diabetes [14][15][16] and it has been found to inhibit insulin secretion from pancreatic islets [17] as well as insulin action in the liver [18][19][20]. Two other important products secreted into circulation by adipocytes are adiponectin and leptin [21,22] that either negatively or positively correlate with body fat mass, respectively.…”
Section: Introductionmentioning
confidence: 99%